The “Secular” in Post-1967 Islamist Thought; Revisiting Arab Intellectual History and Political Ideology towards 20th Century fin-de-siècle - Ihab Shabana (Religions, 2023)
This article gives an historical and analytical account of post-1967 Islamist intellectual production in the Arab-Muslim world and the ways it shaped political ideology in the region. By discussing Islamist approaches and debates with regards to the “secular” and secularism in the Arab-Muslim world the paper tries to answer mainly two research questions: what the perceptions over secularism were after the 1967 Naksa, and how intellectual transformations were applied on political identities, ideologies and strategies by some Islamist parties, occasionally leading to cross-ideological synergies. Using conceptual history, we divide post-1967 into two broad periods, while we argue that Islamist thought copiously appropriated notions of the secular with, however, many limitations.